Household storage and disposal of unused and expired medicines in Dessie, Ethiopia: a cross-sectional study - Yimer, Alebachew; Moges, Getachew; Kahissay, Mesfin Haile (Frontiers in Public Health, 2024)
Introduction: Households frequently store unwanted, unused, or expired medicines in their homes indefinitely or discard them through general municipal waste bins, sinks, or flush them into their toilets. Disposing unused or expired medicines through these unauthorized channels can affect the environment and lives of individuals. This study assessed the household storage and disposal practices of unused and expired medicines in the Dessie City Administration in northeast Ethiopia.Methods: A community-based cross-sectional study was conducted using a semi-structured interview. The data were collected during November 1 -30, 2019. A Multistage sampling technique was employed to recruit participants. The data were analyzed using SPSS version 23.The study found that 62.4% of households stored unused or expired medicines, with analgesics, antibiotics, and cold and flu drugs being the most commonly used. The primary reasons for storing these medicines included future use, discontinuation of medication, and sharing with others, if needed. Most people preferred to dispose of these medicines by trashing them in household garbage, while some disposed of them in their original form and a few diluted them with water before disposal. Multivariate logistic regression analysis identified key factors associated with medicine storage: housewives and government employees were less likely to store unused medicines compared to students and daily workers, and obtaining medicines from private dispensaries was linked to reduced storage. Additionally, households that received advice from physicians were less inclined to store unused medicines.This revealed the widespread storage of unused medicines, primarily analgesics and antibiotics. Improper disposal practices are common and emphasize the need for public education.Employment status, source of medicines, and healthcare advice influenced storage behaviors.Healthcare providers play a vital role in improving medication management and reducing waste.